Extraction, Optimization, and Antioxidant Evaluation of Arginine Deiminase Enzyme in the Escherichia Coli Clinical Isolates - Jawad N. K. Makassees (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Arginine deiminase (ADI) is a promising enzyme with significant therapeutic potential, particularly for its anticancer effects through the depletion of arginine in cancer cells that are auxotrophs. In this study, we aimed to optimize the production of ADI using clinical Escherichia coli isolates and to evaluate its antioxidant activity. A total of 25 E. coli isolates were obtained from 45 hospital samples collected in Wasit Province, Iraq. Optimization of ADI production was performed by systematically testing various factors including culture media, pH, carbon and nitrogen sources, incubation temperature, and time. The antioxidant activity was assessed using the DPPH radical scavenging assay. The highest ADI production was achieved using a modified M9 medium supplemented with 1% w/v sucrose as the carbon source and 5% w/v yeast extract as the nitrogen source. The optimal enzyme activity of 1.6 U/mg protein was observed at pH 7.0, 37°C, and after 24 hours of incubation. The crude ADI extract exhibited high antioxidant activity, with 79.28 ± 1.06% DPPH scavenging at 200 µg/mL, comparable to ascorbic acid, which showed 86.11 ± 1.45% DPPH scavenging. The study successfully optimized the conditions for enhanced ADI production based on clinical E. coli isolates, demonstrating its potential as both an anticancer enzyme and an antioxidant. The dual therapeutic potential of ADI warrants further research, including clinical trials, to explore its application in cancer therapy and as an antioxidant in medical treatments, offering promising avenues for future drug development and improved therapeutic strategies, particularly for targeting cancer and oxidative stress-related diseases.